Журнал «Сельское благоустройство» як джерело до історії підготовки селянської реформи 1861 р. в Лівобережній Україні - Якименко, Л.І. (Культура народов Причерноморья, 2013)
В статті зроблено спробу представити опубліковані на сторінках «Сельского
благоустройства» матеріали, які засвідчують включення дворянства українських губерній в обговорення
важливих соціально-економічних проблем напередодні Селянської реформи 1861 р. Статті
присвячувалися обговоренню майбутньої селянської реформи, «емансипації» поміщицьких селян.
Дописувачі розуміли, що проведення реформи – необхідний процес і у більшості своїй виявили готовність
до емансипації селян.
Навіть побіжний погляд на тексти дворян з українських регіонів засвідчує їх вагомий джерельний
потенціал для вивчення мало дослідженої проблеми участі дворян у підготовці реформи 1861 р.
Ключові слова: Селянська реформа, журнал «Сельское благоустройство», дворянство, селянський
побут, кріпосне право, Полтавська та Чернігівська губернії. В статье сделана попытка представить опубликованы на страницах «Сельского
благоустройства» материалы, которые свидетельствуют о включении дворянства украинских
губерний в обсуждение важных социально-экономических проблем накануне Крестьянской реформы
1861 г. Статьи посвящались обсуждению предстоящей крестьянской реформы, «эмансипации»
помещичьих крестьян. Корреспонденты понимали, что проведение реформы – необходимый процесс и в
большинстве своем проявили готовность к эмансипации крестьян.
Даже беглый взгляд на тексты дворян из украинских регионов свидетельствует о их весомом
потенциале как источника для изучения мало исследованной проблемы участия дворян в подготовке
реформы 1861 г.
Ключевые слова: Крестьянская реформа, журнал «Сельское благоустройство», дворянство,
крестьянский быт, крепостное право, Полтавская и Черниговская губернии. The article is devoted to the review of publications on the pages of the magazine «Rural
improvement» (1858 – 1859), in which the attitudes of noblemen of the left bank Ukraine are presented to the
problem of liberation of peasants and organization of their way of life on the eve of the Great reform.
The Peasant reform in 1861 is attributed to the critical moments of history, which cardinally changed life of the
Russian empire on the whole and Ukrainian lands in particular. What did landlords feel in the moment of
preparation and conducting of reform? What did they consent with and what suggest changing? What did
disturb them?
On these and other questions it is possible to give an answer, examining the paragraphs of the provincial
nobility, which were published on the pages of magazines and newspapers of the epoch of emancipation. A
periodic press review and its analysis gives the picture of that was really interesting to the authors, about their
economic looks, aspirations, organization of way of life of peasants, and so on. Informative potential of such
sources has not been exhausted yet.
It is possible to take the magazine «Rural improvement» to such insufficiently known sources, which practically
found oneself out of research attention. Therefore an attempt to present the materials which certify inclusion of
the nobility of the Ukrainian provinces in the discussion of important socio-economic problems on the eve of the
Peasant reform in 1861 published on the pages of «Rural improvement» is done in this article. The articles were
dedicated to the discussion of future peasant reform, «emancipation» of peasants of landlords and were
accompanied by editorial notes. Correspondents knew the way of life of peasants well, had certain economic
experience and understood that the conduction of reform was a necessary process and in «majority found out
their readiness to emancipation of peasants». Although each of landlords saw this process one's own way.
Even passing glance on the texts of noblemen from the Ukrainian regions, placed on the pages of «Rural
improvement», indicate their significant source potential for studying of little investigational problem of
participation of noblemen in preparation of reform in 1861.
Key words: peasant reform, the magazine «Village's beautification», noblemen, village's mode of life, serfdom,
Poltava and Chernihiv province.